Pemanfaatan Smart Digital Catalog untuk Optimalisasi Promosi Produk pada UMKM Carisco Variasi - Dika Hastanto; Asep Trisna Setiawan; Taqwan Thamrin; Dian Resha Agustina; Wiwin Susanty (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2026)
Micro, Small, and Medium Enterprises (MSMEs) often face challenges in utilizing digital technology to support product promotion activities. Carisco Variasi MSME still conducts promotions conventionally through direct communication or by sending product photos via messaging applications, causing product information to be unstructured and difficult for customers to access. This community service activity aims to implement a Smart Digital Catalog as a digital promotion medium for Carisco Variasi MSME. The implementation method includes needs analysis, system design, web-based system implementation, training, and evaluation through interviews. The results show that the digital catalog system is able to present product information in a structured manner and make it easier for customers to access product information, thereby supporting promotional activities.